2012
DOI: 10.1002/jcp.22926
|View full text |Cite
|
Sign up to set email alerts
|

Parathyroid hormone‐related protein is a hypertrophy factor for human mesangial cells: Implications for diabetic nephropathy

Abstract: Hypertrophy of human mesangial cells (HMC) is among the earliest characteristics in patients with diabetic nephropathy (DN). Recently, we observed the upregulation of parathyroid hormone (PTH)-related protein (PTHrP) in experimental DN, associated with renal hypertrophy. Herein, we first examined whether PTHrP was overexpressed in human DN, and next assessed the putative role of this protein on high glucose (HG)-induced HMC hypertrophy. As previously found in mice, kidneys from diabetic patients showed an incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
17
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 49 publications
4
17
0
Order By: Relevance
“…Equal numbers of cells were lysed in RIPA buffer (0.1% SDS, 0.5% sodium deoxycholate, 1.0% Nonidet P‐40, in PBS) and the total protein content was determined by the Bradford's method (Pierce, Rockford, IL), using BSA as standard. Total protein was expressed as percentage of hypertrophy index (micrograms of protein per 10 4 cells) as previously reported (Romero et al, ; Ortega et al, ). To determine [H 3 ]‐leucine incorporation, podocytes were pulsed with 2 μCi/mL [H 3 ] leucine, washed with PBS, solubilized with 0.1% sodium dodecyl sulfate (SDS) and transferred into a tube containing 10% bovine serum albumin (BSA).…”
Section: Methodsmentioning
confidence: 99%
“…Equal numbers of cells were lysed in RIPA buffer (0.1% SDS, 0.5% sodium deoxycholate, 1.0% Nonidet P‐40, in PBS) and the total protein content was determined by the Bradford's method (Pierce, Rockford, IL), using BSA as standard. Total protein was expressed as percentage of hypertrophy index (micrograms of protein per 10 4 cells) as previously reported (Romero et al, ; Ortega et al, ). To determine [H 3 ]‐leucine incorporation, podocytes were pulsed with 2 μCi/mL [H 3 ] leucine, washed with PBS, solubilized with 0.1% sodium dodecyl sulfate (SDS) and transferred into a tube containing 10% bovine serum albumin (BSA).…”
Section: Methodsmentioning
confidence: 99%
“…There were not enough proteins in the isolated glomeruli to ascertain PTHrP overexpression by Western blot analysis. We and others previously documented that PTHrP can be expressed in activated mesangial cells in vivo and mesangial cells in culture, 11,15,30 as well as in podocytes 31 and endothelial cells. 32 Infiltrating macrophages and T lymphocytes in HSV-damaged glomeruli may be another source of PTHrP, according to previous reports.…”
Section: Discussionmentioning
confidence: 80%
“…A late (day 7) and moderate increase in TGF-b1 mRNA also appeared insensitive to the treatment of mice with PTHrP-neutralizing antibody ( Figure 3B). (24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35) antibody (C13 antiserum) was used for PTHrP immunostaining (green), and a monoclonal mouse anti-human asmooth muscle actin (a-SMA) antibody was used for a-SMA detection (red). Nuclei (blue) were stained by bisbenzimide H33342.…”
Section: Pthrp Is Overexpressed Early In Hsv-induced Glomerulonephritismentioning
confidence: 99%
“…Little is known about the cross-talk between PTHrP and TGF-β1 in the kidney. Previous studies showed that continuous expression of or incubation with PTHrP induced TGF-β up-regulation in MCs and podocytes [ 31 , 32 ]. The present study for the first time demonstrated the dual roles of PTHrP on TGF-β1 signaling.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that prolonged exposure of cultured human MCs to PTHrP in the absence of exogenous growth factors induces a proliferative effect (24 h) followed by hypertrophy at 72 h [ 31 , 33 , 34 ], which is mediated by TGF-β1 [ 31 ]. The biological responses elicited by short PTHrP treatment are as yet unclear.…”
Section: Discussionmentioning
confidence: 99%